The organization of services of orientation to the teaching staff and the improvement of the educational quality - Llerena Companioni, Odalia (Avances en Supervisión Educativa, 2014)
One of the recurrent topics in the current polemics regarding the educational quality in the institutions of superior education, has to do with the faculty’s list whose educational professionalization is a broadly grateful necessity that demands to all educational system to assist the formation and its professors’ permanent upgrade efficiently so that they are able to face the challenges and innovations that take place in the university mark. In this work he/she is carried out a proposal that it considers a new meaning of the services of orientation psychopedagogical from a bigger premeditation in their to work toward the faculty’s orientation, that which transforms him into a valid alternative because it considers the contribution of resources, methodologies, technical, strategies and activities to the pedagogic professional development of the professors contributing to the improvement of the institutional educational quality.